A cross-sectional study of frequency and factors associated with dog walking in 9-10 year old children in Liverpool - Gareth Stratton (BMC Public Health, 2013)
Westgarth C, Boddy LM, Stratton G, German AJ, Gaskell RM, Coyne KP, Bundred P,McCune S, Dawson S.